The Last Chance Saloon - Hong, Ye; Zhang, Hongtao; Gartner, Anton (Frontiers in Cell and Developmental Biology, 2021)
Accurate chromosome segregation requires the removal of all chromatin bridges, which link chromosomes before cell division. When chromatin bridges fail to be removed, cell cycle progression may halt, or cytokinesis failure and ensuing polyploidization may occur. Conversely, the inappropriate severing of chromatin bridges leads to chromosome fragmentation, excessive genome instability at breakpoints, micronucleus formation, and chromothripsis. In this mini-review, we will briefly describe the origins of chromatin bridges, the toxic processing of chromatin bridges by mechanical force, and the TREX1 exonuclease. We will then focus on the abscission checkpoint (NoCut) which can confer a transient delay in cytokinesis progression to facilitate bridge resolution. Finally, we will describe a recently identified mechanism uncovered in C. elegans where the conserved midbody associated endonuclease LEM-3/ ANKLE1 is able to resolve chromatin bridges generated by various perturbations of DNA metabolism at the final stage of cell division. We will also discuss how LEM-3 dependent chromatin bridge resolution can be coordinated with abscission checkpoint (NoCut) to achieve an error-free cleavage, therefore acting as a ‘last chance saloon’ to facilitate genome integrity and organismal survival.